PERANCANGAN ULANG FORMULIR RAWAT JALAN BERDASARKAN KEBUTUHAN PENGGUNA DI RS DKT Dr.SOETARTO YOGYAKARTA - , JESSICA FEBYOLANDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : medical record is a summary of the facts of the history of the life and health of the patient, including old diseases and illnesses now as well as its treatment, written by health professionals who take care of these patients (Huffman,1994) . Based on the above understanding can be described that the medical record is a source release of patient health information for getting services. To support the needs of logging necessary facilities or medical record-keeping means that either that chick a good medical record. The content of the medical record according to your needs and will help simplify the process of recording information, therefore it takes a form as required in the content of the medical record. In addition to viewing the form in terms of the content of the medical record of outpatient services, in need of a notice form the physical aspect, anatomik, content and function of medical record without reducing the information that should be loaded. The purpose of design: Redesign the form record the appropriate outpatient medical needs by improving existing items in it and focused on aspects of anatomik, contents, and physical form in order to simplify and speed up the process of service without compromising the basic functions of the medical record. Design process: the design starts with the collection of data relating to outpatient medical record form, define the theory of the design of the form used. Design by sketching out an alternative form, to create an image design, mewujudka design and conducted trials and election form The result of design: design of outpatient medical record generated refers to users needs and focus to simplify and facilitate the use of form and quality, a stronger paper.